2012
DOI: 10.5846/stxb201108011126
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rhizosphere microbial community structure of weak and strong allelopathic rice varieties under dry paddy field

Abstract: Terminal restrain fragment length polymorphism (T鄄RFLP) technique was employed to investigate the microbial community structure and composition in the rhizosphere of weak and strong allelopathic rice varieties directly sowing on dry paddy field at 5鄄leaf stage and 7鄄 leaf stage. The results showed that 9-87 TRFs and 15-89 TRFs were detected from the soil DNA digested with two restriction enzymes Hae 芋 and Msp 玉, respectively. The rank鄄abundance of TRFs from different samples showed extremely significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…This may be speculated that phenylpropanoid metabolism is weak in 'Suihua'. He et al (2012) and Xiong et al (2012) detected higher expression of the genes involved in the phenylpropanoid metabolism and correspondingly higher contents of phenolic compounds in the allelopathic rice cultivar PI312777, which were consistent with the higher rates of Echinochloa crusgalli L. inhibition attributed to this variety.…”
Section: Discussionsupporting
confidence: 72%
“…This may be speculated that phenylpropanoid metabolism is weak in 'Suihua'. He et al (2012) and Xiong et al (2012) detected higher expression of the genes involved in the phenylpropanoid metabolism and correspondingly higher contents of phenolic compounds in the allelopathic rice cultivar PI312777, which were consistent with the higher rates of Echinochloa crusgalli L. inhibition attributed to this variety.…”
Section: Discussionsupporting
confidence: 72%
“…The unique microecological environment is composed of plants, root exudates, and root microorganisms, which cause allelopathy [36][37][38][39][40][41][42]. Previous studies have demonstrated that the community and population of bacteria, fungi, and actinomycetes significantly differed in the rhizosphere soil of allelopathic and non-allelopathic rice under the mediation of different exudates [22,32]. Accordingly, phenolic acids and terpenes could specifically aggregate certain microorganisms [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that allelopathy in rice might result from the interaction of alleochemicals with specific microorganisms in rhizosphere soil [28][29][30][31]. Therefore, extensive studies have focused on assessing the interaction between allelopathic rice and rhizosphere microorganisms [19,22,32], including the separation and identification of allelochemicals. Thus, what other substances, besides phenolic acids and terpenoids, are allelochemicals?…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids, flavonoids and momilactones have all been 14 found to be degraded and transformed in the soil of paddy fields (Blum 2011;15 Kato-Noguchi & Peters 2013; Weston & Mathesius 2013). Our recent study found 16 that the allelopathic rice variety PI312777 recruited more microbial populations than 17 less allelopathic rice did, and the main genera of microbes in rice rhizosphere belongs 18 to myxobacteria (Xiong et al 2012). Myxococcus sp.…”
Section: Accepted Articlementioning
confidence: 97%